Peer Influences: Risk Factors to Voluntary and Non-Voluntary Clients to Remain Abstinence - Amin Al Haadi Shafie; Abdul Rashid Abdul Aziz; Mizan Adiliah Ahmad Ibrahim; Amer Fawwaz Bin Mohamad Yasid; Nur Amalina Binti Abd Laziz (Human Resource Management Academic Research Society, 2024)
Indexed by ERA